Prevalence and aetiological profiles of facial nerve paralysis: A five-year review of tertiary Health institutions in Kano state, Northwestern Nigeria - Gbiri, Caleb Ademola (Journal of Community and Health Sciences, 2020)
Aims: To determine the prevalence and aetiological profiles of facial paralysis in Kano, Nigeria. Methods: This study involved three tertiary and health institutions in Kano, Nigeria between January 2006 and December 2010. Out of 11145 patients’ records, 1003 cases had indication of facial nerve paralysis but 936 met the inclusion criteria. Data were extracted using research pro-forma. Data was analyzed using z-test for proportional significance, and Chi square test at 0.05 significant levels. Results: Prevalence rate of facial paralysis was 9.1% and mostly common (48.1%) between age of 20-38 years with males (52.8%) and the married (71.2%) more affected. Left side of the face was involved more frequently (53.0%) than the right side (46.4%) and bilateral (0.6%). Lower motor neuron lesion type (74.1%) was more common. Most common co-morbidity associated with facial paralysis was infections, closely followed by diabetes mellitus and pre-eclampsia. Highest incidence was in the year 2010, and the least was in 2006. z-values showed that minor difference in the prevalence exist between male and female. There was an association between each of age, occupation, co- morbidities and place of residence and the aetiologic factors. However, the strength of relationships was weak and the degree of association is very weak as determined using Cramer V and Lambda. Conclusion: Prevalence of facial paralysis is relatively high in this region. It is affected by urban dwelling, being a full- housewife and co-morbidity. Lower motor neuron type and sudden onset were predominant. This calls for greater awareness for preventive measures.